Antimicrobial Effect of Newly Formulated Toothpastes and a Mouthrinse on Specific Microorganisms: An In Vitro Study - Guven, Yeliz; Ustun, Nilufer; Tuna, Elif Bahar; Aktoren, Oya (European Journal of Dentistry, 2019)
Objective The aim of this in vitro study was to assess the antimicrobial properties of newly formulated toothpastes (four toothpastes for adults and two toothpastes for kids/babies) and a mouthrinse.Materials and Methods Newly formulated six different toothpastes and one mouthrinse of a single brand and commercially available five toothpastes and three mouthrinse were investigated for their antimicrobial activity against two oral pathogens, Streptococcus mutans and Candida albicans, by agar well diffusion assay. After incubation, the inhibition zone diameters were measured in millimeters and statistical analyses were performed.Results All experimental adult toothpastes exhibited good antimicrobial activity against S. mutans and C. albicans except the experimental toothpaste D. Experimental toothpaste B exhibited the highest antibacterial activity against C. albicans and S. mutans. Experimental toothpaste for kids showed the best antimicrobial activity against S. mutans when kids’ toothpastes were compared. None of the tested toothpastes for kids/babies showed antibacterial effects for C. albicans. Among the mouthrinse tested, Sensodyne mouthrinse showed the best results. Experimental mouthrinse showed significantly lower antibacterial activity against S. mutans then Sensodyne, Eludril, and chlorhexidine mouthrinse.Conclusion Although experimental toothpaste and mouthrinse formulations revealed good results in terms of antimicrobial activity to some specific microorganisms, further studies involving more bacterial species or analyzing the quality and efficacy of these products by other in vitro or in vivo tests are needed.
Keywords: antimicrobial activity; Candida albicans; mouthrinse; Streptococcus mutans; toothpaste